How are children who are delayed in the Childhood Vaccination Programme vaccinated: A nationwide register-based cohort study of Danish children aged 15–24 months and semi-structured interviews with vaccination providers. Issue 1 (February 2020) - Pedersen, Kenneth B.; Holck, Marie E.; Jensen, Aksel K.G.; Suppli, Camilla H.; Benn, Christine S.; Krause, Tyra G.; Sørup, Signe
Aims: Delay of childhood vaccinations is common and influences efforts to reduce targeted diseases. In Denmark, the diphtheria, tetanus, pertussis, polio and Haemophilus influenzae type b (DTaP-IPV-Hib) vaccine is recommended at ages 3, 5 and 12 months and the first measles–mumps–rubella vaccine (MMR-1) at 15 months. Following guidelines, children delayed at age 15 months should receive MMR-1 and DTaP-IPV-Hib-3 simultaneously, unless DTaP-IPV-Hib-2 was received less than 6 months ago, when MMR-1 alone is recommended. We studied compliance with these guidelines and the reasons for non-compliance with a focus on vaccination providers. Methods: We used a nationwide register-based cohort study of children born in Denmark between January 2000 and June 2013, who were lacking MMR-1 and DTaP-IPV-Hib-3 at age 15 months and were followed to 24 months. We also performed semi-structured telephone interviews with vaccination providers. Results: The study consisted of 156, 921 children (18% of the children born in the period). Among the 40, 060 children who had received DTaP-IPV-Hib-2 less than 6 months ago, 37, 892 (95%) received MMR-1 alone. Among the 88, 469 children who had received DTaP-IPV-Hib-2 more than 6 months ago, 6334 (7%) received DTaP-IPV-Hib-3 and MMR-1 simultaneously. The interviews indicated that some vaccination providers are reluctant to give multiple vaccinations at the same visit and some have a preference of following the usual sequence in the programme. Conclusions: Vaccination providers generally complied with the recommended minimum 6 months' interval between DTaP-IPV-Hib-2 and DTaP-IPV-Hib-3. Conversely, there was a low compliance with the recommendation to administer DTaP-IPV-Hib-3 and MMR-1 simultaneously. More efforts are needed to ensure timely vaccination.